A list of Syriac Orthodox ecclesiastic ordinations from the sixteenth and seventeenth century - Bcheiry, Iskandar. (Piscataway, NJ)
vii, 135 sayfa
Keywords: “The Bodleian Library in Oxford currently holds an unpublished historical document in Syriac containing precious historical information about the ordination of bishops, priests, monks, and deacons. Bcheiry gives the text and translation, and focuses on the importance of the data found in this historical list which he compares with other historical data found in other sources“ -- Yayıncı.